Portrait photograph of an unidentified man (Boston, MA) - Thayer, Alexander Wheelock, 1817-1897 (previous owner):::Collector::::::::::::; Warren's (photographer):::Photographer:::::::::::: (Boston, MA; United States; Warren's, 2023)
Portrait photograph of an unidentified man (undated) from the studio of Warren's 289 Washington Street, Boston, MA, from the personal collection of Alexander Wheelock Thayer.